2009
DOI: 10.1055/s-0029-1222605
|View full text |Cite
|
Sign up to set email alerts
|

Biological Influence of Physical Exercise on Hemostasis

Abstract: Some of the benefits of physical activity may result from effects on hemostasis. However, the increased burden of cardiovascular complications and sudden death occurring during and immediately after exercise prompts investigation to elucidate the biological relationship between physical exercise and hemostatic function. Although both the hemostatic and fibrinolytic systems are strongly influenced by physical exercise, the outcomes of available studies to date are biased by several confounding variables, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 64 publications
6
89
1
3
Order By: Relevance
“…For example, monocytes decreased significantly following flight, contrary to our prediction, which was based upon increases in monocytes following exercise in humans (Nieman et al, 2003;Pedersen and Hoffman-Goetz, 2000;Nieman et al, 2001) and during migration in some passerine birds (Hegemann et al, 2012b). Additionally, thrombocytes were unaffected by flight, even though platelet number and coagulability increase in humans after exercise (Lippi and Maffulli, 2009). These contrasts may reflect deep taxonomic divisions, differences in relative intensity of the exercise, or both.…”
Section: Effects Of Flightcontrasting
confidence: 79%
See 1 more Smart Citation
“…For example, monocytes decreased significantly following flight, contrary to our prediction, which was based upon increases in monocytes following exercise in humans (Nieman et al, 2003;Pedersen and Hoffman-Goetz, 2000;Nieman et al, 2001) and during migration in some passerine birds (Hegemann et al, 2012b). Additionally, thrombocytes were unaffected by flight, even though platelet number and coagulability increase in humans after exercise (Lippi and Maffulli, 2009). These contrasts may reflect deep taxonomic divisions, differences in relative intensity of the exercise, or both.…”
Section: Effects Of Flightcontrasting
confidence: 79%
“…(2) Based on post-exercise changes in humans and mammals, eosinophils and monocytes should increase following flight. (3) By analogy with human studies, thrombocytes should increase post-flight because, immediately after exercise, human platelet numbers increase and blood shows 'hypercoagulability' (Lippi and Maffulli, 2009). (4) Natural antibody titres should decline post-flight because lymphocyte function and immunoglobulin levels typically fall after intense exercise (see also Nebel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that exercise intolerance predicts a poor physical ability to perform tasks of daily living [12]. Besides, regular physical exercise produces a variety of beneficial effects on health, such as increased longevity, decreased mortality and incidence of metabolic disorders, among other comorbidity [13].…”
Section: Discussionmentioning
confidence: 99%
“…Since moderate physical exercise is known to lower the risk of cardiovascular diseases [9,10], we were interested to study the effect of moderate physical exercise on both concentration and pro-coagulant activity of circulating MP.…”
mentioning
confidence: 99%